2016
DOI: 10.1183/13993003.00443-2016
|View full text |Cite
|
Sign up to set email alerts
|

Global Lung Function Initiative 2012 reference equations for spirometry in the Norwegian population

Abstract: We studied the fit of the Global Lung Function Initiative (GLI) all-age reference values to Norwegians, compared them with currently used references (European Community for Steel and Coal (ECSC) and Zapletal) and estimated the prevalence of obstructive lung disease.Spirometry data collected in 30 239 subjects (51.7% females) aged 12-90 years in three population-based studies were converted to z-scores.We studied healthy non-smokers comprising 2438 adults (57.4% females) aged 20-90 years and 8725 (47.7% female)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
103
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(120 citation statements)
references
References 35 publications
14
103
1
2
Order By: Relevance
“…Table 4 presents the main characteristics and results of some studies reporting Z-scores data [1420] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 presents the main characteristics and results of some studies reporting Z-scores data [1420] .…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, some authors opted for their use to interpret spirometry, for example in the Australasian [16] , Norwegian [20] , German [18] and French [17] populations. On the other hand, the GLI-2012 norms seem unsuitable for clinical use in the Swedish [14] , Finnish [19] and Brazilian [22] populations.…”
Section: Introductionmentioning
confidence: 99%
“…LANGHAMMER et al [4] used data from 11 496 Norwegian subjects across an age range of 12-90 years who were healthy never-smokers without symptoms. They found that the median z-scores for FEV1, FVC and FEV1/FVC were essentially zero in those aged <20 years, with female adults tending to have very slightly better FEV1 and FVC and lower FEV1/FVC than the values predicted by GLI-2012 (median z-scores 0.15, 0.25 and −0.17, respectively).…”
Section: @Erspublicationsmentioning
confidence: 99%
“…The European Respiratory Society has sponsored the Global Lung Function Initiative (GLI) in obtaining coherent reference equations for spirometry appropriate for all ages [2] and advocates these being the standard applied for spirometry within Europe. In this issue of the European Respiratory Journal (ERJ), two groups of European researchers have looked at their local populations to see if the GLI-2012 equations were a satisfactory fit and so can be safely used for clinical decision making [3,4].…”
Section: @Erspublicationsmentioning
confidence: 99%
See 1 more Smart Citation